Teacher-student relationship in the Educational thoughts of Confucius - Thushiyanthan, V.; Thileepan, R.T. (South Eastern University of Sri Lanka, 2021)
Teacher- student relationship is considered to be the most important aspect in Educational thoughts. The concept of Confucius on this subject was well known even 2500 years ago. However, at present his stand is under scrutiny and also has become an important subject of discussion. Therefore, it has been imperative to examine teacher, student relationship based on the thoughts of Confucius. This research is a critical analysis of the importance of teacher, student relationship in the present time based on the thoughts of Confucius. The role of teachers, the students' obligation and matters related to them. Confucius combined students and leaders in his Educational system. At present among the three theories given recognition in China. The Educational thought of Confucius is also recognized. This shows the greatness of his thoughts. Therefore, this study critically analyses the importance of his Educational thoughts and its relevance for today. The thoughts of Confucius aim at making students exemplary citizens of the society. His thoughts on Education emphasizes that they should reach the leaders and others in society. He believed that if sound Education is given to leaders of the country Education will reach each and every one. Beside that by giving Education to students the future generation will become enlightened. The sources of this study work on Confucius, research papers, literatures and data gathered from wed sites. As methodologies a competitive study, critically analysis and descriptive method are used.
Keywords: Confucius; Educational Thoughts; Teacher; Student; Relationship